Analisis Literasi Informasi Mahasiswa Semester 1 Program Studi Ilmu Perpustakaan dan Informasi Islam IAIN Kerinci Berdasarkan Model The Big6TM - Astuni Rahayu; Dian Maisaroh (Perpustakaan Universitas Gadjah Mada, 2026)
Information literacy is an important competency in higher education because it relates to students' ability to find, evaluate, and use information effectively. This study aims to analyze the level of information literacy of first- semester students in the Islamic Library and Information Science Study Program at IAIN Kerinci and identify the factors that influence it. The study used a descriptive quantitative approach with a survey method using an information literacy pre-test instrument based on the Big6™ information literacy model. The study respondents were 26 first-semester students in the Islamic Library and Information Science Study Program at IAIN Kerinci. The results showed that 58.34% of students were in the low literacy category, 33.33% were in the medium category, and only 8.33% were in the high category. These findings indicate a gap between the availability of scientific information sources and students' ability to utilize them. The main factors influencing low information literacy include students' academic culture that relies more on general search engines, minimal information literacy training, limited use of information technology, and the lack of integration of information literacy into the learning process. This study recommends strengthening information literacy programs through regular workshops, collaboration between lecturers and librarians, and optimizing the use of library e-resources.